Kejadian Depresi Postpartum Pada Ibu Yang Menikah Dini - Siti Balqis; Fitriani Mediastuti; Rofiqoh Widiastuti (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2022)
Background: Postpartum depression is a psychiatric disorder that came a few days or thefirst week after birth. Postpartum depression though indirectly cause mortality but can causepain or morbidias to mother and child. Psychic disorders called postpartum depression canbe affected by characteristics of the mother's age. The factor of postpartum depression is inthe teenage years or <20 years. Indonesia is the country with the highest percentage ofyoung marriage age in the world (ranked 37) and the second highest in ASEAN. In DIY,Gunung Kidul is high enough percentage of birth in teens. Purpose of this research was todetermine the incidence of postpartum depression in women who married early in Pacarejo Semanu Gunungkidul.Method: Quantitative survey research type is descriptive. Sampling with accidental samplingtechnique with the number of respondents 50 mothers who married early and had given birth.The instrument used was a questionnaire Edinburgh Postnatal Depression Scale (EPDS).Result: Based on the characteristics of the respondents, the majority married aged 20 years(26.0%), SMPN majority educational level (72.0%), job housewife majority (82.0%),primiparous parity majority (88.0%), and the majority of normal childbirth (96.0%). The resultsof research as many as 20 respondents did not postpartum depression, 16 respondents mildpostpartum depression, 9 respondents moderate postpartum depression, and 5 respondentssevere postpartum depression. Psychosocial background factors concerning age, parity,education, employment, and the type of labor may be a factor contributing to postpartumdepression in women who married early.Keywords: Characteristics, Postpartum Depression, EPDS